Cutting distance as factor to evaluate the quality of wood machined surfaces: A preliminary study - Aguilera, Alfredo; Rolleri, Aldo; Burgos, Francisco (Maderas. Ciencia y Tecnología, 2025)
Surface quality of solid wood products is an important subject of study since it influences further manufacturing processes, such as finishing or strength of adhesive joint. In this study, the surface quality of the machined surfaces was evaluated through the cutting distance, which is defined as the accumulated linear meters of wood processed by a cutting tool. The roughness (Rz) and wetting (contact angle) behaviour on wood machined surfaces have been assessed each 2000 meters respectively, from 0 to 10000 meters. In Pinus radiata samples, machined using a three hydro centred mounting cutter-heads of 6 knives HSS (High Speed Steel) 6 % W (Wolfram) and a rake angle of 15° each, similar contact angles were found associated to different values of Rz through the cutting distance. This study verifies that a wide spectrum of cutting distance allows an accurate evaluation of roughness and wettability behaviour surface characteristics.